Suffix caching: an approach to ensure data availability in P2P streaming systems. (11th March 2009) - Alustwani, H.; Bahi, J.M.; Mostefaoui, A.
The now emerging Peer-to-Peer (P2P) streaming systems suffer from a data unavailability problem resulting from the unpredictable peers departure. This paper describes our suffix caching approach to overcome this problem. We use an embedded Distributed Virtual Cache (DVC) amongst the peers to temporarily save the 'last part' (suffix) of 'now playing' videos, that are most likely to be watched to the end by some users. We leverage on efficient allocation policy that 'fairly' distributes the suffixes over the DVC. We dynamically adjust the size of the suffixes to the system workload by using a closed-loop feed back control system.